2019
DOI: 10.3389/fped.2019.00222
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hypertension in CAKUT: Protective Factor for CKD

Abstract: Patients with congenital kidney and urinary tract abnormalities (CAKUT) will often develop end-stage renal disease at some point and the need for renal replacement therapy is associated with high rates of morbidity and mortality. Hence, efforts to slow the progression of the disease are essential. Hypertension has been proven to be an independent risk factor for faster decline of glomerular filtration rate in renal patients, but studies involving only children with CAKUT are scarce. We performed a literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
(66 reference statements)
0
4
0
1
Order By: Relevance
“…Hypertension is another concerning public health problem, which is an independently associated factor for CKD in all investigated subjects, but not in sub-group of DM subjects without MAFLD. As hypertension is a common disease affecting almost all human systems, and a leading cause of CKD, [28][29][30] the risk in the subgroup might have been eliminated by other factors, such as diabetes, hyperuricemia, being overweight.…”
Section: Dovepressmentioning
confidence: 99%
“…Hypertension is another concerning public health problem, which is an independently associated factor for CKD in all investigated subjects, but not in sub-group of DM subjects without MAFLD. As hypertension is a common disease affecting almost all human systems, and a leading cause of CKD, [28][29][30] the risk in the subgroup might have been eliminated by other factors, such as diabetes, hyperuricemia, being overweight.…”
Section: Dovepressmentioning
confidence: 99%
“…Modifiable risk factors, such as obesity, smoking, or diabetes, should be avoided as much as possible because of their associations with hypertension, albuminuria, and kidney function deterioration [11,23,24,27]. For diabetes, hypertension, and cardiovascular disease, a direct relation with faster development of CKD was shown in patients with SFK [18,28,29].…”
Section: Additional Hitsmentioning
confidence: 99%
“…A number of studies have shown that high BP plays the role of an independent risk factor for rapid reduction in glomerular filtration rate (GFR) in patients with renal diseases [6][7][8][9]. BP monitoring is important for the management of patients with CKD, both for the conventional cardiovascular risk reduction and long-term preservation of kidney function [8]. The parameters of 24-hour ambulatory blood pressure monitoring (ABPM) have more pronounced predictive value for the diagnosis of target organ damage than…”
Section: Introductionmentioning
confidence: 99%
“…Оригінальні статті / Original Articles the indicators determined at a single office/home BP measurement [8,10].…”
Section: Introductionunclassified
See 1 more Smart Citation